Ambulantage et services à la mobilité : les carrefours commerciaux à mexico - Jérôme Monnet; Angela Giglia; Guénola Capron (Cybergeo, 2007)
Among various urban changes, the intensification of intra-urban mobility is characteristic of the contemporary phenomenon known as metropolization. In this context, we examine here the services brought to everyday urban travellers, through the study of the so-called informal commerce or street vending, in selected crossroads in Mexico City’s metropolitan area. We established a classification that, in spite of the fluidity and fuzziness of activities, allows us to understand how the retail offer is precisely adapted to urban life paces, to traffic modes and to the social and geographical features of connecting places.